Influence of Community Characteristics and Perception Against the Comfort Level of the Bike Path Sudirman Street, DKI Jakarta - Utoyo Harjito; Lita S. Barus (Budapest International Research and Critics University, 2022)
The bicycle mode of transportation is an environmentally friendly vehicle, does not cause air pollution and supports sustainable development. Cycling is the second best mode of transportation after buses which will become a fashion in the future. Cities where bicycle infrastructure is added will increase bicycle users by 48 percent, and when compared to other cities that do not add bicycle lanes, this is already greater. In this study, multiple regression analysis was used to show the influence of characteristics as well as people's perceptions of the convenience of the bicycle lane on Jalan Sudirman, DKI Jakarta. The results showed that there was an influence of public perception on the level of comfort of the bicycle lane. The bicycle mode of transportation being the most inclusive and sustainable is the easiest and cheapest.